Egg consumption and cardiovascular disease among diabetic individuals: a systematic review of the literature - Tran NL (Dove Medical Press, 2014)
Nga L Tran, Leila M Barraj, Jacqueline M Heilman, Carolyn G ScraffordExponent Center for Chemical Regulation and Food Safety, Washington, DC, USABackground: This study reviewed epidemiological and experimental evidence on the relationship between egg consumption and cardiovascular disease (CVD) risks among type II diabetes mellitus (T2DM) individuals, and T2DM risk in nondiabetic subjects.Results: Four of the six studies that examined CVD and mortality and egg consumption among diabetics found a statistically significant association. Of the eight studies evaluating incident T2DM and egg consumption, four prospective studies found a statistically significant association. Lack of adjustment for dietary confounders was a common study limitation. A small number of experimental studies examined the relationship between egg intake and CVD risk biomarkers among diabetics or individuals with T2DM risk factors. Studies among healthy subjects found suggestive evidence that dietary interventions that include eggs may reduce the risk of T2DM and metabolic syndrome.Conclusion: Differences in study design, T2DM status, exposure measurement, subject age, control for confounders and follow-up time present significant challenges for conducting a meta-analysis. Conflicting results, coupled with small sample sizes, prevent broad interpretation. Given the study limitations, these findings need to be further investigated.Keywords: type II diabetes mellitus, diet, cardiovascular risk factors, coronary heart disease, stroke